FAMILY COMMUNICATION PATTERNS IN THE FORMATION OF ADOLESCENT CHARACTER IN CENGKEH TURI VILLAGE, BINJAI CITY - Vira Ade Natasya; Muaz Tanjung (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
This study aims to describe family communication patterns in shaping the character of adolescents in the Cengkeh Turi Sub-district of Binjai City. Adolescence is a developmental phase that is vulnerable to biological, psychological, and social changes, thus requiring effective communication within the family. Amidst the busyness of parents and the increasing use of gadgets by adolescents, the intensity of direct communication within families has changed and has impacted the process of instilling values and character formation. This study used a descriptive qualitative approach involving seven families consisting of seven parents and seven adolescents who were selected purposively. Data were obtained through in-depth interviews and observations, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that a dialogical or two-way communication pattern is more dominant, where parents not only give orders but also provide explanations and space for adolescents to express their opinions. This communication pattern contributes to the formation of adolescent character, particularly in the aspects of discipline, responsibility, openness, and religiosity. Conversely, one-way communication patterns tend to result in obedience but do not encourage openness. Thus, open and responsive family communication plays an important role in shaping adolescent character..